AN ANALYSIS OF PRESUPPOSITION FOUND IN THE GUARDIAN NEWS: PRAGMATICAL APPROACH - Siahaan, Crisnova Katalonika; Mubarak, Zia Hisni (JEE (Journal of English Education), 2020)
This paper is qualitative descriptive research which investigates types of presupposition and the mostly used type of presupposition. The data source in this study is utterance in Guardian news. The method of collecting is by observation. The methods of analyzing data are by agih and padan method from Sudaryanto. Author uses theory of Yule which divides presupposition into 6 types these are existential presupposition, factive presupposition, lexical presupposition, structural presupposition, non-factive presupposition, and counterfactual presupposition. The researcher has 20 data here. There are 3 types of presupposition found in the Guardian news. The most used type used is existential presupposition.